In your shoes: A qualitative study on the perspectives of professional dancers and staff regarding dance injury and its prevention - Bolling, C.; van Rijn, R. M.; Pasman, H. R.; van Mechelen, W.; Stubbe, J. H. (Translational Sports Medicine, 2021)
This study explored the perspectives of dancers and staff of the Dutch National Ballet, regarding injury definition, injury risk factors, and preventive measures. We conducted two focus groups: one with the medical/artistic staff and another with dancers. Data were analyzed inductively by two independent coders, through the constant comparative method, based on Grounded Theory. Participants defined an injury based mainly on dance performance limitations, while pain and time loss reflected injury severity. Dance injury was described as a spectrum of injury levels that depend on the ability to perform to the best of their ability, pain levels, and potential modification on dance participation. The imbalance between workload and the dancers' capacity to deal with load was perceived as the main cause related to injuries. Workload was presented as a complex equation, combining consistency, repertoire demands, daily schedule, traveling plan, and their interrelations. Injury prevention was described as a dynamic balance between being prepared to deal with load and managing load. The critical factors that modulate the injury prevention process were as follows: teamwork, communication, experience, and planning. Our findings show injury is not defined by a clear cutoff, with multiple injury risk factors interacting and evolving, making injury prevention a constant challenge.